Socialising Tourism Rethinking Tourism for Social and Ecological Justice - Higgins-Desbiolles, Freya; Doering, Adam; Bigby, Bobbie Chew (Taylor & Francis, 2021)
socialising tourism; social tourism; ecological justice; social justice; values; ethics